2023
DOI: 10.1186/s12885-023-10593-z
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ANRIL promotes HR repair through regulating PARP1 expression by sponging miR-7-5p in lung cancer

Abstract: Background Radiotherapy is an important treatment for lung cancer, mainly by triggering DNA double-strand breaks to induce cell death. Blocking DNA damage repair can increase the radiosensitivity of tumor cells. Recent studies have identified long noncoding RNAs as key regulators in DNA damage repair. The lncRNA ANRIL was previously shown to be involved in homologous recombination (HR) repair, but its specific mechanism has not been fully elucidated. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Since ANRIL has been described to be a key regulator in DNA damage repair (HDR), it is well suited to play a role in this process. In agreement, ANRIL positively acts on HDR by modulating the miR-7-5p/PARP1/RAD51 and miR-145-5p/MMP1 pathways in LC and TNBC respectively [ 100 , 228 ].…”
Section: Anril Activitiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Since ANRIL has been described to be a key regulator in DNA damage repair (HDR), it is well suited to play a role in this process. In agreement, ANRIL positively acts on HDR by modulating the miR-7-5p/PARP1/RAD51 and miR-145-5p/MMP1 pathways in LC and TNBC respectively [ 100 , 228 ].…”
Section: Anril Activitiesmentioning
confidence: 87%
“…In the context of CRC, ceRNA activity of ANRIL has been proposed to promote resistance to 5-Fluorouracil by inhibiting the ABCC1/let-7a pathway [ 247 ]. Finally, ANRIL may favor cisplatin resistance in LC and OS by modulating the miR-328/ABCG2/MDR1 and miR-125a-5p/STAT3 signaling pathways, respectively [ 125 , 228 ].…”
Section: Anril Activitiesmentioning
confidence: 99%
“…However, recent findings in the literature seem to support our hypothesis of an epigenetic mechanism of action. Indeed, a study has identified PARP-1 as a target of miR-7-5p in a model of lung cancer cells, demonstrating that sponging miR-7-5p promotes the homologous repair (HR) path through upregulating PARP1 expression [21]. In another study, Garmutin-A (GA), an NP isolated from Garcinia multiflora, induced apoptosis via the upregulation of miR-17-5p, triggering PARP-1 downregulation, in leukemic CB3 cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…20 ANRIL has been discovered to enhance homologous recombination (HR) repair, which is achieved by regulating the expression of poly(ADP-ribose) polymerase 1 (PARP1) through its interaction with miR-7-5p, effectively acting as a microRNA sponge. 21 Until now, there is no evidence regarding the regulation of miRNA by the ANRIL in HAPE. We observed that ANRIL exhibited a negative regulatory effect on miR-181c-5p in hypoxic PMVECs.…”
Section: Discussionmentioning
confidence: 99%
“…The report shows that the inhibition of ANRIL has been shown to hinder the cisplatin resistance in lung cancer, which is achieved through up‐regulation expression of miR‐98 20 . ANRIL has been discovered to enhance homologous recombination (HR) repair, which is achieved by regulating the expression of poly(ADP‐ribose) polymerase 1 (PARP1) through its interaction with miR‐7‐5p, effectively acting as a microRNA sponge 21 . Until now, there is no evidence regarding the regulation of miRNA by the ANRIL in HAPE.…”
Section: Discussionmentioning
confidence: 99%